2001
DOI: 10.1002/pola.1208
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the volume phase transition in poly(n‐isopropylacrylamide) gels prepared under high pressure

Abstract: New poly(N‐isopropylacrylamide) gels were prepared under high pressure (ca. 200 MPa) during gelation. The preparation‐pressure dependence of the deswelling speed of the gels was measured with a conventional T‐jump method. The deswelling time of a gel rod 2.2 mm in diameter prepared at 193 MPa was about 200 s, 1000 times faster than that of a homogeneous poly(N‐isopropylacrylamide) gel. Moreover, the collective diffusion coefficient, the thermal fluctuation, and the ensemble‐average intensity of the swollen gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…23,29 Kitada and co-workers have shown that the characteristic time for these processes can be altered by manipulating the pressure during gelation. 30 Incorporation of hydrophobic comonomers with NIPAM can also lead to gels with a sigmoidal shrinking behavior. 31 Visual observations indicate that all of these effects stem from either heterogeneities in the gel or formation of a dense skin layer that restricts outward permeation of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,29 Kitada and co-workers have shown that the characteristic time for these processes can be altered by manipulating the pressure during gelation. 30 Incorporation of hydrophobic comonomers with NIPAM can also lead to gels with a sigmoidal shrinking behavior. 31 Visual observations indicate that all of these effects stem from either heterogeneities in the gel or formation of a dense skin layer that restricts outward permeation of water.…”
Section: Resultsmentioning
confidence: 99%
“…The exact nature of the departure has been reported to depend on the chemical and physical structure of the gel. For example, shrinking of PNIPAM gels cross-linked with MBAA near T c has been known to occur in multiple stages with different rates of water loss. , Kitada and co-workers have shown that the characteristic time for these processes can be altered by manipulating the pressure during gelation . Incorporation of hydrophobic comonomers with NIPAM can also lead to gels with a sigmoidal shrinking behavior .…”
Section: Resultsmentioning
confidence: 99%